Power systems frequency estimation using amplitude tracking square wave for low-end protective relays - Ukil, Abhisek (2020)
Growing emphasis on the disturbance-free electrical power distribution demands for economical and efficient smart estimation techniques in the automation architectures of the future medium voltage (MV)/ low voltage (LV) distribution networks. Unlike high-end protective relays which are typically used in the high voltage transmission systems, low-end economical protective relays are suitable for the MV/LV distribution networks. Frequency estimation is one of the pre-requisites of the electrical protective relays in such systems. The low-end protective relays demand for computationally efficient signal processing algorithms for frequency estimation thus eliminating the need to integrate sophisticated hardware components and advanced software routines. In this paper, time-domain based frequency estimation is proposed, which is focused for the implementation in the low-end relays for MV/LV distribution networks. Frequency estimation is based on the novel amplitude tracking square wave (ATSW), which is fast and sensitive to disturbances in the monitored signal. Performance of the ATSW for frequency estimation is analyzed on the recorded real-world disturbance signals as well as on the various simulated case studies. Simplicity of the ATSW for low-end relays is substantiated by comparative analysis with the existing frequency estimation techniques. In addition to the frequency estimation, versatility of the ATSW is substantiated by application for transient state detection in the AC and DC power systems.